1994
DOI: 10.1007/bf00201038
|View full text |Cite
|
Sign up to set email alerts
|

Phenyllactic acid but not tropic acid is an intermediate in the biosynthesis of tropane alkaloids in Datura and Brugmansia transformed root cultures

Abstract: Abstract. (S)-(-)-Tropic acid is the acidic moiety of the tropane ester alkaloids, hyoscyamine and scopolamine (hyoscine). When tropic acid is fed to transformed root cultures of Datura stramonium L. or a Brugmansia (Datura) candida • B. aurea hybrid, the formation of these alkaloids is inhibited. Phenyllactic acid, from which the tropoyl moiety is derived, is considerably less inhibitory. Label from (RS)-phenyl[1,3-13Cjlactic acid is incorporated at high levels into apoatropine, littorine, aposcopolamine, hyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The rate of 13 C enrichment was calculated from the areas under the M+1, M+2 and M+4 ions (as described by Robins et al 1994). …”
Section: Quantification Of Incorporationmentioning
confidence: 99%
“…The rate of 13 C enrichment was calculated from the areas under the M+1, M+2 and M+4 ions (as described by Robins et al 1994). …”
Section: Quantification Of Incorporationmentioning
confidence: 99%
“…Moreover, 1‐O‐β‐glucose esters can be produced by UDP‐glycosyltransferase (UGT) using specific substrates and UDP‐glucose (Schulenburg et al , ; Zhao et al , ). Previous research identified A. belladonna enzymes responsible for producing acetylpseudotropine, tigloylpseudotropine, and phenylacetylpseudotropine, but not for acetyltropine or phenylacetyltropine (Robins et al , ), suggesting that BAHD acyltransferases, taking CoA activated compounds, participate in acyl modification of pseudotropine but not tropine. Thus, glycosylated phenyllactate (phenyllactylglucose) might be the acyl donor for tropine, and tropine and phenyllactylglucose might condense to littorine when catalysed by serine carboxypeptidase (SCP)‐like acyltransferases (SCPL‐ATs), which catalyse esterification between specific compounds and 1‐O‐β‐glucose esters (Li & Steffens, ).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, tropinone reductase I reduces tropinone to tropine, which leads to the biosynthesis of hyoscyamine and scopolamine. Tropine is then condensed with a phenyllactic acid moiety to form littorine, which undergoes P450-mediated rearrangement to hyoscyamine aldehyde (Robins et al, 1994;Li et al, 2006;O'Connor, 2010). An uncharacterized alcohol dehydrogenase is proposed to convert hyoscyamine aldehyde to hyoscyamine, which is subsequently converted to scopolamine in a two-step epoxidation reaction catalyzed by hyoscyamine 6-hydroxylase (H6H) (Matsuda et al, 1991;Hashimoto et al, 1993).…”
Section: Introductionmentioning
confidence: 99%